COVID-19 and Food Safety FAQ: Is Coronavirus a Concern at Grocery Stores? (Mandarin Chinese) - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS)
This is the Mandarin Chinese translation of FSHN20-20/FS348: COVID-19 and Food Safety FAQ: Is Coronavirus a Concern at Grocery Stores?. It provides answers to a few frequently asked questions regarding COVID-19 and grocery stores. Written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman, and published by the UF/IFAS Food Science and Human Nutrition Department, May 2020.